BLOOD GLUCOSE LEVEL AND PANCREAS HISTOLOGICAL SECTION OF MICE ( Mus musculus L.) INDUCED BY ALLOXAN AFTER TREATMENT OF Curcuma mangga Val. RHIZOME EXTRACT - Madihah, Madihah; Alfina, Fitriani; Gani, Yetti Yusri (Jurnal Biologi Udayana; Vol 20 No 2 (2016): Jurnal Biologi, 2016)
Herbal-based drug development for diabetes mellitus continues to grow in order to find alternatives of theuse of synthetic drugs which is relatively expensive. The present study examined the potency of temu mangga(Curcuma mangga Val.) rhizome extract in decreasing blood glucose levels and repairing histological damage ofpancreas endocrine gland in male mice (Mus musculus L.) Swiss-Webster that has been induced by alloxan. Theexperimental method with 5 treatments and 5 replications were used. The dose of alloxan was 200 mg/kg bw,while the dose of temu mangga extract were 100, 200, 400 and 800 mg/kg bw. The measured parameters werethe body weight, fasting blood glucose levels by using blood glucose tolerance test, and the percentage of pancreatic? cells that undergo necrosis. Data were analyzed by ANOVA with 95% confidence level and continued withDuncan’s multiple range tests. The results showed no difference on body weight of test animals in all treatments.The reduction percentage of fasting blood glucose levels from temu mangga rhizome extract by dosage of 400mg/kg bw (48.712%) was significantly different from the treatment of alloxan (0.588%) (p<0.05). The percentageof ? cells that undergo necrosis from temu mangga rhizome by dosages of 200, 400, and 800 mg/kg bw weresignificantly different with alloxan (22.75±3.68 %) (p<0.05). In conclusion, temu mangga rhizome extract bydosage of 400 mg/kg was optimum to decrease blood glucose levels and repair the pancreas histological damagein mice that were induced by alloxan.
Keywords: fasting blood glucose level, temu mangga, ? cell pancreas,